205k views
5 votes
Enter the correct answer in the box. Write the sum of √28x^6 + 4√7x^6 in simplest form, if x ≠ 0.

2 Answers

3 votes

Answer:

21.97025026/250

User FuSsA
by
6.0k points
4 votes

The simplest form of the sum of the expression is 6x³√7

Surds are the square root of non perfect squares. Examples of perfect squares are 9, 16, 4, 25 e.t.c

Examples of surds are ; √50, √28 e.t.c

Solving the expression

√28x⁶ + 4√7x⁶

= √ 4 × √ 7x⁶ + 4√7x⁶

= 2√7x⁶ + 4√7x⁶

Represent √7x⁶ by y

= 2y + 4y

= 6y

2√7x⁶ + 4√7x⁶ = 6√7x⁶

= 6x³√7

Therefore, the simplest form of the sum of the expression is 6x³√7

User Kevin Seifert
by
5.8k points